HIDROGENASI MINYAK KEDELAI DENGAN VARIASI MASSA KATALIS PALLADIUM - Adi Permadi; Totok Eka Suharto (Agroindustrial Technology Journal, 2023)
Soybean oil, also known as vegetable oil, consists of triglycerides such as saturated and unsaturated fatty acids. However, this soybean oil has low oxidative stability when stored at room temperature and used at high temperatures. Hydrogenation is carried out to obtain oxidation stability and will reduce double bonds including trans fatty acids. The use of palladium catalyst is the most potential in the hydrogenation process. This research was conducted in two conditions, experiment 1 and experiment 2. With temperature conditions of 75oC, pressure of 1 atm, using a reactor equipped with a stirrer at a speed of 450-520 rpm. In experiment 1, the palladium catalyst was not activated and hydrogen gas entered through the bottom of the reactor. In experiment 2, the palladium catalyst was activated with NaOH while hydrogen gas entered through the side of the reactor. Iodine number analysis method used is the Wijs method. The results of experiment 1, so that the value of the iodine number can be below 100 gr I2/gr of oil, while in the results of experiment 2, the value of the lowest iodine number is at a value of 110 gr I2/g of oil. The main influencing factors in our research a hydrogen gas turbulence, palladium catalyst activation and stirring.